2022
DOI: 10.3390/nano12172963
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model of CVD Growth of Graphene on Cu(111) Surface

Abstract: Although the CVD synthesis of graphene on Cu(111) is an industrial process of outstanding importance, its theoretical description and modeling are hampered by its multiscale nature and the large number of elementary reactions involved. In this work, we propose an analytical model of graphene nucleation and growth on Cu(111) surfaces based on the combination of kinetic nucleation theory and the DFT simulations of elementary steps. In the framework of the proposed model, the mechanism of graphene nucleation is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…By analyzing the occurrence map (Figure 4) and the frequency of events, we can conclude that C and C 2 species played the primary role in graphene growth under the considered conditions. This observation is in line with the findings of a recent study that used analytical kinetic modeling to investigate graphene nucleation and growth [58]. The inclusion of ring closure reactions in the reaction set is essential for the accurate simulation of graphene growth pathways, which we will discuss in more detail in the following section.…”
Section: The Growth Mechanismsupporting
confidence: 83%
See 3 more Smart Citations
“…By analyzing the occurrence map (Figure 4) and the frequency of events, we can conclude that C and C 2 species played the primary role in graphene growth under the considered conditions. This observation is in line with the findings of a recent study that used analytical kinetic modeling to investigate graphene nucleation and growth [58]. The inclusion of ring closure reactions in the reaction set is essential for the accurate simulation of graphene growth pathways, which we will discuss in more detail in the following section.…”
Section: The Growth Mechanismsupporting
confidence: 83%
“…Since Li et al reported activation energy barriers of the set of reactions happening during the CVD of graphene on Cu(111) using CH 4 and H 2 as precursors [64], we firstly analyzed the impact of the DFT method choices on the energy values. As pointed out in our previous study, we found strong co-adsorption effects on the activation energy barrier, especially for reactions on the slab edge [58]. In particular, the activation energy barrier of C 2 attachment to the edge (one of the three most crucial reactions in the growing process) was doubled with an increase of the supercell, i.e., 1.22 eV instead of 0.58 eV, which was reported by Li et al [53].…”
Section: Activation Energy Barrierssupporting
confidence: 79%
See 2 more Smart Citations